The Ashaninka Culture and its Ancestral Pedagogical Manifestations - Medrano Osorio, Rubén Américo (2022)
The purpose is to describe the manifestations of the Asháninka pedagogical culture from its ancestry, and to interpret the transmission of knowledge of teaching in its formation from social practice in the formative sense. under the interpretive epistemological approach and grounded theory. The study is of a descriptive ethnographic level and 20 families were taken as a sample. The technique was the in-depth interview through key informants and interview guides. Conclusion: Ashaninka culture is current and recreated through ancestral wisdoms through orality, pedagogy is perceived in the division of teaching around girls and boys, cosmogonic knowledge and conservation of their culture.